2002
DOI: 10.1023/a:1020048327158
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The productivity of local chickens under village management conditions was studied in six villages situated in three climatic zones within Morogoro District in Tanzania. Two villages were picked in each climatic zone (warm and wet, warm and dry, cool and wet) for the study. The data were obtained by actual measurement, qualitative observations and interview of members of the households directly responsible for the care of chickens. In addition, data sheets were given to selected farmers to record the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 5 publications
3
19
1
1
Order By: Relevance
“…While clutch size was not related to body length and shank length of hens (r<0.4, p>0.05), there was a significant correlation between body weight and clutch size (r = 0.66, p<0.05). The differences in body weight and body measures between male and female birds are in agreement with reports from Tanzania (Mwalusanya et al, 2002) and Zimbabwe (Mcainsh et al, 2004); such differences are due to the differential effects of androgens and estrogens on growth (Yakubu et al, 2009). The higher body weight of male and female chickens in DF than in the other AEZ might be attributed to less efforts needed by these birds to scavenge their feed: DF farms are smaller-sized than farms in the other AEZ but characterized by highly productive vegetable cultivation, potentially offering plenty of nutritious residues.…”
Section: Results and Disscussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While clutch size was not related to body length and shank length of hens (r<0.4, p>0.05), there was a significant correlation between body weight and clutch size (r = 0.66, p<0.05). The differences in body weight and body measures between male and female birds are in agreement with reports from Tanzania (Mwalusanya et al, 2002) and Zimbabwe (Mcainsh et al, 2004); such differences are due to the differential effects of androgens and estrogens on growth (Yakubu et al, 2009). The higher body weight of male and female chickens in DF than in the other AEZ might be attributed to less efforts needed by these birds to scavenge their feed: DF farms are smaller-sized than farms in the other AEZ but characterized by highly productive vegetable cultivation, potentially offering plenty of nutritious residues.…”
Section: Results and Disscussionsupporting
confidence: 89%
“…The hens produced on average 5.2±0.23 clutches per year with a total of 12.3±2.85 eggs per clutch (range 8 to 14), resulting in 64.5±6.91 eggs per hen and year. The latter value was higher than that reported for local chicken in Bangladesh (44; Baru and Yoshimur, 1997) and Uganda (40 to 50; Ssewannyana et al, 2008), while it was similar to the production reported from Tanzania (Mwalusanya et al, 2002) and Botswana (Badubi et al, 2006). The proportion of hatched eggs per clutch was 88.1±6.01% with significant differences between EH (92.9±7.16) and the other AEZ (p<0.05).…”
Section: Results and Disscussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Husbandry practices characterized by the use of rustic animals in free range conditions with a low capital investment, which enables assuming a relatively low economic risk to implement an efficient productive management to produce high-biological-value protein sources such as meat and eggs [8,9]. Additionally, these products are preferred among consumers because of their pigmentation, taste, and lean quality of meat [10,11]; which translates into acceptable income that returns to each family, closing the cycle [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous chickens also possess the ability to not only rely on provided feed, but also thrive in extensive and rural setups, rummaging for natural food sources throughout the day and thus offer a more organic and affordable protein source [88,120,121]. They can be successfully reared under extensive production conditions, with minimal inputs [122,123]; which allows them to freely express their natural be haviour. Additionally, these chickens can effectively make use of limited space and natural protein sources (such as insects) for their nourishment [88,121], providing them wider nutritional sources to satiate hunger.…”
Section: Mitigation Strategy 2: Promotion Of Hardy and Climate Resilimentioning
confidence: 99%